Fabrication And In Vitro Evaluation of Buccal Mucoadhesive Tablet of Antihypertensive Drug - Ghumre, Purva Madhukar; Suryakant Awate, Shyam; R. Arote, Sanjay (Journal of Neonatal Surgery, 2025)
The buccal route offers excellent opportunities and potential advantages for systemic drug delivery as compared to per-oral administration. The present study involves designing, developing, and optimizing the buccal tablet formulation of Carvedilol (CA) by using the QbD approach. The Carvedilol buccal tablets were prepared using the dry granulation method. Based on the DoE, the composition of the optimized formulation of CA BT consists of 20 mg of CA, 10 mg Carbopol 934p, 17.75 mg HPMC K100, 15 mg Chitosan, 30 mg PVP K-30, 1 mg Magnesium stearate, 15.25 mg Mannitol, 1 mg Aspartame, and 50 mg Ethyl cellulose. The optimized formulation of CA BT 18 was found to have a mucoadhesive strength of 22.28±0.35 g, a swelling index of 79.35 ± 0.35%, and drug release was sustained up to 10th h, compared to the marketed product, the release was up to 8h. The drug release kinetics were best explained by the Korsmeyer Peppas plot, which demonstrates drug release by stress-induced swelling and slow erosion from the polymer. An attempt was made to design a buccal tablet of Carvedilol individually for sustained drug release in the treatment of hypertension. The formulation can be given in case of a patient who cannot take medication orally, in trauma, and unconscious patients. The development of a new pharmaceutical product is very time-consuming, extremely costly, and high-risk, with very little chance of a successful outcome. Hence, in the study already marketed drug product Carvedilol was chosen as a buccal drug delivery system by a novel approach using QbD tools to target the quality product accurately.